2021
DOI: 10.1007/s40258-021-00674-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Health Economic Evaluations in Mainland China: A Comparison of Peer-Reviewed Articles in Chinese and in English

Abstract: Background Health and education are two closely related factors that affect human development. A limited number of studies have been conducted in China, most of which have been based on small sample sizes and with inconsistent results. The study investigates the association between mortality rate and educational level in China based on the sixth national population census in 2010.Methods This is large-scale population study based on the nationally administrated data sets of population census in 2010, 2000 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 82 publications
1
1
1
Order By: Relevance
“…There was a significant difference between the average quality scores of the studies published in Chinese and those published in English. The findings also were consistent with Jiehua Cheng et al [ 25 ]. This difference may be because the editors of Chinese journals did not require authors to report standardized economic evaluations nor to supplement their details.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There was a significant difference between the average quality scores of the studies published in Chinese and those published in English. The findings also were consistent with Jiehua Cheng et al [ 25 ]. This difference may be because the editors of Chinese journals did not require authors to report standardized economic evaluations nor to supplement their details.…”
Section: Discussionsupporting
confidence: 92%
“…Before our study, a study including pharmacoeconomic research from 2003 to 2014 in China reported a mean score of 18.7 assessed using the same CHEERS checklist, which had 1.02 higher than the score of our study [ 20 ]. The Jiehua Cheng et al study showed that the average quality score of the included studies in China from 2006 to 2015 was 56.59 ± 16.90 [ 25 ], less than 74.63 ± 12.75 from our study. The reporting quality on China’s published economic evaluation studies of negotiated oncology drugs in 2020 latest NRDL may have been improved, but it is still lower than some studies.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation